Analisis Tes Proyektif dan Tes Objektif dalam Asesmen Kepribadian (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This article examines the roles and applications of various types of psychological tests in personality assessment, particularly contrasting projective tests with objective tests. Psychological tests are not intended to determine pass or fail outcomes, but rather to gain a deep understanding of an individual’s psychological aspects. Projective tests, such as the Rorschach Inkblot Test and the Thematic Apperception Test (TAT), are utilized to reveal latent personality traits through ambiguous stimuli. In contrast, objective tests like the Minnesota Multiphasic Personality Inventory (MMPI) and the Edwards Personal Preference Schedule (EPPS) are designed to produce consistent and quantifiable data. This study employed a library research method, reviewing both primary and secondary sources to provide a comprehensive overview. In counseling practice, the choice of psychological test depends on the assessment goals and the client's conditions. The article emphasizes the necessity for professional competence and ethical considerations, including cultural sensitivity and the ability to accurately interpret test results.